TEACHER VARIABLES AND SENIOR SECONDARY STUDENTS’ ACHIEVEMENT IN MATHEMATICS IN RIVERS STATE, NIGERIA - Daso, Peter Ojimba (European Scientific Journal, ESJ, 2013)
This research study focused on the relationship between teacher variables and students’ achievement in mathematics at a senior secondary II level in Rivers State, Nigeria. The ex-post facto research design was adopted for this study, since already conducted mathematics test scores of the students were retrieved and used for the analysis. Furthermore data were elicited through the teacher variables and students’ achievement in mathematics questionnaire (TVAMQ). A population of 10,373 senior secondary II students and teachers were involved in the study, out of which 4510 students and 151 teachers were chosen for the sample using the Yarrow Yamen’s formula. The data were analyzed using the Z-test statistic, means and percentages. The findings were that there is a significant relationship between teachers’ method of teaching, teachers’ attitude and students’ achievement in mathematics. Hence recommendations were made.